New record of the fringed leaf frog, cruziohyla craspedopus (Anura: Phyllomedusidae) extends its eastern range limit - Fraga, Rafael de; Torralvo, Kelly (Acta Amazonica, 2019)
The fringed leaf frog, Cruziohyla craspedopus is rarely sampled in the Brazilian Amazon, probably due to low detection probability associated with its arboreal habit. The knowledge about the species’ distribution stems from successive additions of occasional occurrence records, which indicate that the species is widely distributed throughout Amazonia. We present new occurrence records to update the geographic range of the species, which is hereby extended 224 km to the northeast. We also present morphological data from collected specimens and discuss the updated range from the geographic and ecological points of view. We show that the range of the leaf frog crosses several main tributaries along the southern bank of the Amazonas River, although the species occurrence is apparently limited by a minimum tree cover of 70%. © 2019, Instituto Nacional de Pesquisas da Amazonia. All rights reserved.
Novo registro de ocorrência da perereca-franjada, Cruziohyla craspedopus (Anura: phyllomedusidae) estende o limite oriental de sua distribuição